INCORPORATING OPERATIONAL EXCELLENCE STRATEGY INTO COMPANY FINANCIAL PERFORMANCE IN OIL AND GAS INDUSTRY: AN EMPIRICAL STUDY - Ciptono, Wakhid Selamet (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
The objective of this research is to test the effect of Quality Management Practices (QMP) based on Deming's 14 points, Operational Excellence Strategy (OE), on company financial pettotmsnce (CFP). Conceptual model of Deming's Principle is used with operational excellence strategy (operational excellence dimensions and investment level) as mediating variables between the independent variables of Quality Management Practices and the dependent variable of company financial pertormance. The survey instrument usede comprehensive set of 81 importance and performance questions that were directly tied to the eight constructs of the study.In summary, eight causal paths specified in the hypothesized model were found to be positive and statistically significant. Furthermore empirical results suggest that quality management practices have a positive and significant indirect effect on company financial performance through its direct effect on operational excellence strategy. The results also show that a complete model ftt and the acceptable parameter level which indicate the overall parameter are good fit between the hypothesized model and the observed data. By concentrating on a single industry (oil and gas) is that Structural Equation Modeling (SEM) specification of the sequentialrelationship model between eight research constructs can be more complete and specific because unique characteristics of the oil and gas industry can be included (e.g. upstream and downstream chain activities). Finally, the particular design of the research and the findings suggest that the final structural model of the study has a great potential for replication to manufacturing as well as service operations.Based on the oil and gas managers (the SBU level), operational excellence strategy (five meaningful factors of operational excellence) can be viewed as the effective use of production and operations capability and technology for achieving business and corporate goals. Operational excellence strategy, therefore, is to help a company's operations organization define the common ground where it can play a proactive and collaborative role with other company functions or cross-functional relationships.Oil and gas managers in Indonesia can use these meaningful factors of operational excellence in concert with other critical quality management practices to help them in their word-class company initiatives. Researchers can also use these factors to build structural model linking such factors to various organizational performance measures (i.e., non-financial or value- gain and financial or monetary-gain performances).